Efektifitas Penerapan Absensi Sidik Jari (Finger Print) Dalam Meningkatkan Kedisiplinan Pegawai (Asn) Kabupaten Sinjai - Imran Imran; Darmawati Darmawati; Fitriani Fitriani; Kiki Rasmala Sani (Journal of Innovative and Creativity, 2025)
This research aims to assess how effective the implementation of the fingerprint attendance system is in enhancing employee discipline in Sinjai Regency. With a qualitative descriptive approach, data were obtained through interviews and observations in the Regional Civil Service Agency environment. The results of the study indicate that the fingerprint attendance system has a positive impact on the level of ASN discipline, although there are several technical obstacles such as power and fingerprint reading problems. This system is considered fair, transparent, and encourages employee order and accountability.